PEMBERDAYAAN KELOMPOK KERJA (POKJA) IBU RUMAH TANGGA DALAM MONITORING KESEHATAN WARGA SELAMA COVID-19 - Wawan Kurniawan (Jurnal AKAL : Abdimas dan Kearifan Lokal, 2020)
To ensure the effectiveness of the Covid-19 Health Protocol regulations by the central government, communication is needed starting from a small scope, namely the Rukun Tetangga (RT). One of the roles at the RT level is the monitoring stage to identify, record, and report residents with symptoms of COVID-19 to RW using an online device through the Covid-19 Task Force. In RT.03 RW14 Perum BDB2 Siukahati Cibinong Bogor the role of the Covid-19 Task Force is played by a housewife working group (pokja). Community service partners are housewives working group (pokja).  The formulation of the problem is how the efforts of RT residents in community health monitoring activities run well through housewives poka? The purpose of writing this paper is to ensure the monitoring process and the health of citizens during Covid-19 is running well. The method of implementing community health monitoring during the Covid-19 pandemic by this RT mother working group is the Plan, Do, Check, Action (PDCA) method. At the Plan stage, it is determined that the implementer of the activity is a group.In the Plan stage, it is determined that the implementer of the activity is a working group (pokja) of RT mothers, at the Do stage the monitoring process is applied by distributing the Citizen Health Entry Form through the WA group and verification through direct monitoring, at the Check stage is Checking the questionnaire results is very important to ensure the health of citizens by taking the whole data instead of sampling data and the Act stage is to provide information about healthy lifestyles, provide spiritual support and support, provide staple food assistance for casual workers and isolate independent citizens who are included in the ODP. The conclusion of this paper is that the empowerment of housewives working group (pokja) in monitoring and community health during covid-19 is running effectively.